The Error-Related Negativity. (March 2018) - Gehring, William J.; Goss, Brian; Coles, Michael G. H.; Meyer, David E.; Donchin, Emanuel
We look back on the events surrounding the genesis of our 1993 article on the error-related negativity (ERN), a component of the event-related brain potential that accompanies errors in the performance of speeded-response tasks. Our reminiscences focus on the personal friendships, intellectual influences, and chance occurrences that shaped the article. To put our work in historical context, we consider subsequent trends in neuroimaging, computational modeling, and psychiatry that gave the ERN high visibility and contributed to the longevity of its scientific interest.